The Ethiopian and Eritrean Evangelical Diaspora of Montreal: Music, Identity and Ambivalence - Ferran, Hugo (African Diaspora, 2015)
The Ammanuel Montreal Evangelical Church (amec) is composed of over 150 members of Ethiopian and Eritrean origin. Through the examination of their musical practices, this article analyzes how music is involved in the construction and expression of religious identities in the context of migration. It appears that in borrowing worship music widespread in Ethiopia and in its diaspora, the faithful highlight the "Ethiopianness" of the group, at the expense of the minority Eritrean identity. The author then reveals that each musical parameter conveys different identity facets. If the universality of the Gospel message is expressed through dance and lyrics, the repertoire and its instrumentarium convey the "Ethiopianness" of the congregation, while the rhythms refer to a multi-ethnic Ethiopian imaginary. As for the local identity (Montreal) of the congregation, it is represented by the combination of several hymns borrowed from the stars of Ethiopian Gospel music. Finally, the paper highlights some musical ambivalences of the faithful who, in the context of migration, feel torn between several cultures.